Quantitative analysis of the completeness of medical records documents for inpatient general surgery patients at X Padang Hospital - Dewi Oktavia (Institute of Computer Science (IOCS), 2023)
The quality of medical records is an indicator of the quality of hospital services which can be seen from the completeness of filling out medical record documents. Incompleteness in filling out medical record documents will disrupt administrative order which will affect the patient treatment process, where officers will have difficulty identifying the patient, officers will have difficulty determining the next treatment or therapy action that will be carried out on the patient. Based on the results of the initial survey at Hospital X Padang, it was found that a quantitative review of medical record documents had never been carried out. The aim of this study was to determine the results of a quantitative review of the completeness of medical records for general surgery inpatients. This research method is descriptive with a quantitative approach. The population and sample in this study were documents from inpatients specifically for general surgery in the fourth quarter of 2021, with a total sample of 38 documents. The research location is at Hospital the doctor's hand was 94.7%, the method of recording abbreviated items was 73.7%. From the results of the quantitative analysis research, it was concluded that it still does not meet the Minimum Service Standards, namely 100%. To increase the completeness of filling out medical records, it is hoped that hospitals can create reward and punishment policies, implement rules or SOP guidelines for filling out medical record documents.